Penentuan Kadar Nitrogen Fosfor dan Kalium dari Serat Pelepah Sagu (Metroxylon sago) - Hesti; Rahmanpiu; Ratna (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
Research has been carried out to determine the levels of nitrogen, phosphorus, and potassium from sago midrib fiber (metroxylon sago). This study aims to determine the levels of nitrogen, phosphorus, and potassium from sago midrib fiber and its feasibility as a planting medium. The result of the nitrogen content using the kjeldahl method were carried out in three stages, namely the destruction stage, the distillation stage and the titration stage with a concentration of 0,21%. Result of phosphorus content by UV-Vis spectrofotometer method is 0,06%. Then the result of potassium levels using the atomic absorption spectrofotometer (AAS) method were 0,0615. From the result obtained, the content of the sago midrib fiber does not meet the requirements as a growing medium used today. However, sago midrib fiber has the potential as a growing medium used today because it contains NPK nutrients, although in very low amounts.